RANCANG BANGUN SISTEM PENDIAGNOSA PENYAKIT OSTEOPOROSIS PADA WANITA MENGGUNAKAN METODE FUZZY INFERENCE SISTEM TSUKAMOTO - Arfida, Septilia; Siahaan, Maruli Tua (Jurnal Informatika, 2016)
Osteopororsis is rotten bones, which is a disease that signed by the shortage of low bone mass, also bone micro arsitexture disorder and decreasing of bone tissue quality. Those signs causes bone fragility therefore it is easily broken. Osteoporosis can be detected by certain tool through radiology chek up. Because the tool is still limited and also the check up and the tool quite expensive, so the community do not understand the osteoporosis disease. The diagnose system application of osteoporosis at women uses Tsukamoto Fuzzy Inference System method. This method is choosen to do the diagnose of osteoporosis has 5 variables, such as age, activity, calsium, height, and weight. Each variable has 3 fuzzy group, from all group it is taken 27 fuzzy rules and then used in inference step. At inference step, it is searched the antecendent membership value (Î±) and diagnose score (z) from each rule. This system creates recommendation value which is the information of the diagnose of osteoporosis therefore it is able to know the type of osteoporosis that is suffered. Beside that it also gives the information of how to handling and treatment of osteoporosis.Â Key Words :Osteoporosis, Fuzzy Logic, Fuzzy Inference System TsukamotoÂ